2021
DOI: 10.2478/jvetres-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii in retail fresh meat products from free-range chickens in Spain

Abstract: Introduction Toxoplasma gondii is one of the most prevalent zoonotic protozoan parasites worldwide and affects the vast majority of warm-blooded animal species, including humans. Postnatal infection in humans occurs through the ingestion of sporulated T. gondii oocysts or via the oral intake of parasite tissue cysts during the consumption of raw or undercooked meat. In this regard, given their high exposure to oocysts, chickens (Gallus domesticus) raised on the ground co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…All 216 samples had satisfactory internal control amplifications; positive control amplified correctly in each run. As previously observed ( Gracia et al, 2021 ), the sensitivities of both sets of primers, ToxoRoc and ToxoRepeat, for the 529 bp repeat element were similar. Parasite DNA amplification was observed in 53/216 samples and no amplification was observed in 163/216 samples.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…All 216 samples had satisfactory internal control amplifications; positive control amplified correctly in each run. As previously observed ( Gracia et al, 2021 ), the sensitivities of both sets of primers, ToxoRoc and ToxoRepeat, for the 529 bp repeat element were similar. Parasite DNA amplification was observed in 53/216 samples and no amplification was observed in 163/216 samples.…”
Section: Resultssupporting
confidence: 87%
“…DNA extraction and the qPCR protocol were performed according to procedures detailed in previous studies ( Gracia et al, 2021 ) with some modifications. Genomic DNA was extracted from a 200 μL volume of the concentrated samples using a commercial Speedtools DNA extraction kit (Biotools B&M Labs S.A, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports showed that by using qPCR, Brucella melitensis and Brucella abortus in different samples, including raw milk and cheese, could be determined accurately so as to predict the potential health adversity of the corresponding samples [ 192 , 193 , 194 ]. And zoonotic parasites including Toxoplasma gondii were also determined using qPCR so as to prevent any potential risks that might be caused [ 195 ].…”
Section: Strategies To Predict Prevent the Microbial Risks Of Livesto...mentioning
confidence: 99%
“…Food animals are reservoirs of T. gondii and one of the sources of parasite transmission to humans giving T. gondii its medical and veterinary importance ( Tonouhewa et al , 2017 ). Humans get infected by consuming raw or uncooked meat containing tissue cysts, contaminated food or water with oocysts; or, from mother to fetus through vertical transmission in a primary infection ( Hamilton et al , 2019 ; Salinas et al , 2021 ). More than a third of the world’s population has been infected with T. gondii which can have serious consequences for immunodeficient or immunocompromised people ( Mao et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%